Redes de cooperação do estado do Rio Grande do Sul: um estudo dos motivos de participação das empresas em redes - Becker, Deisi Viviani (2007)
At the present scenario, one of the solutions found by micro, small and even medium-sized enterprises to retake their growth, development and competitiveness has been the nets. This alternative may result in more development of the enterprises through a proposal of joint growth, which is a strategy of cooperation that aims to provide competitive advantages. The research had as objective verify the reason of the company enter in the net and if this objective be reached. Our research was concentrated in 117 enterprises that take part in the Nets of Cooperation proposed by the Business Development and International Affairs Department (SEDAI) of the government of Rio Grande do Sul (RS), in partnership with the University of Santa Cruz do Sul (UNISC) and the Federal University of Santa Maria (UFSM). This sample was restricted to the enterprises that belong to the four biggest nets in number of associates from the two regions where the universities are located: the region of the Vale do Taquari and Rio Pardo and the region of the center of the state, respectively. Through a questionnaire, it was possible to verify the reasons that led the enterprises to join the nets and wheter their goals were being reached. The search of opportunities and the minimization of costs were found to be their main aims, while the sharing of resources (technological, management and human resources), leadership in the net and trust are in second plan. Another aspect that called attention mentions to it the referring answers to the number of associates in the nets, detailing that one of the reasons that had made with that the searched entrepreneurs entered the nets was the high number of associates and not it low number as the theories point that it is one of the forms of development and reduction of internal conflicts.The content of this work is organized in six chapters: introduction, characterization of nets and the main international experiences, the reasons for joining the nets, methodology, analysis of the results and finally, concluding remarks with some suggestions for further studies